Atypical Somatic Symptoms in Adults With Prolonged Recovery From Mild Traumatic Brain Injury - Stubbs, Jacob L.; Green, Katherine E.; Silverberg, Noah D.; Howard, Andrew; Dhariwal, Amrit K.; Brubacher, Jeffrey R.; Garraway, Naisan; Heran, Manraj K. S.; Sekhon, Mypinder S.; Aquino, Angela; Purcell, Victoria; Hutchison, James S.; et al. (Frontiers in Neurology, 2020)
Somatization may contribute to persistent symptoms after mild traumatic brain injury (mTBI). In two independently-recruited study samples, we characterized the extent to which symptoms atypical of mTBI but typical for patients suffering from somatization (e.g., gastrointestinal upset, musculoskeletal and cardiorespiratory complaints) were present in adult patients with prolonged recovery following mTBI. The first sample was cross-sectional and consisted of mTBI patients recruited from the community who reported ongoing symptoms attributable to a previous mTBI (n = 16) along with a healthy control group (n = 15). The second sample consisted of patients with mTBI prospectively recruited from a Level 1 trauma center who had either good recovery (GOSE = 8; n = 32) or poor recovery (GOSE < 8; n = 29). In all participants, we evaluated atypical somatic symptoms using the Patient Health Questionnaire-15 and typical post-concussion symptoms with the Rivermead Post-Concussion Symptom Questionnaire. Participants with poor recovery from mTBI had significantly higher ‘atypical’ somatic symptoms as compared to the healthy control group in Sample 1 (b = 4.308, p < 0.001) and to mTBI patients with good recovery in Sample 2 (b = 3.169, p < 0.001). As would be expected, participants with poor outcome in Sample 2 had a higher burden of typical rather than atypical symptoms (t(28) = 4.750, p < 0.001, d = 0.88). However, participants with poor recovery still reported atypical somatic symptoms that were significantly higher (1.4 standard deviations, on average) than those with good recovery. Our results suggest that although ‘typical’ post-concussion symptoms predominate after mTBI, a broad range of somatic symptoms also frequently accompanies mTBI, and that somatization may represent an important, modifiable factor in mTBI recovery.